A probabilistic analysis of border node-based MFR routing protocol for vehicular ad hoc networks. (2015) - Raw, Ram Shringar; Lobiyal, Daya K.; Das, Sanjoy
In this paper, we examined the significance of position-based routing with border-node-based forwarding for vehicular ad hoc network (VANET) to optimise path length between vehicles. We have mathematically evaluated the performance of border node-based forwarding method such as Border node-based MFR (B-MFR). B-MFR strongly avoids the interior nodes within the transmission range for further transmitting the packets. Furthermore, we have developed a mathematical model for B-MFR to determine average number of hop counts, expected distance between source and destination, and maximum progress of the next-hop node towards the destination node using Poisson distribution for node deployment. Analytical and simulation results indicate that B-MFR can provide efficient routing in VANETs. In our work, results clearly show that using the border-nodes is an advantage to maximise the performance of routing protocol in terms of average number of hops with minimum delay. We have mathematically simulated the proposed protocol in MATLAB and compared the result with existing routing protocol MFR.